PENERAPAN METODE PEMBELAJARAN BLENDED LEARNING TERHADAP HASIL BELAJAR MAHASISWA DI INSTITUT PENDIDIKAN TAPANULI SELATAN PADANGSIDIMPUAN - Lukman Hakim Siregar (Jurnal Education and Development, 2019)
This researct is purpose to know about the blended learning method to the result of student learning outcomes. The population is 40 people and tissue which is used sampling total collecting technique it is 40 people.This research use descriptive method about the application of blended learning modle and main material. Of linear ecuation system is to variable. In data analysis use qwestionnaire and test experiment. Analysis data result is gotten T arihtmatic = 3,27where as T table = 1,67 with real standard 5%. We know that a T arithmetic is bigger than T table that is (3,27< 1,67) this result means the alternative hyphotesis is accepted of it’s validity. According to analysis result which is done, we have got average value the application of blended learning modle to the result of student learning outcomes with good categories. The lecturer have to appropriate learning modle in prodi pendidikan matematika who are 3rd semester. And I suggest to the college students must study hard to understand lesson especially in main material about computer application.